Prediction and prevention of ventilation impairments during bronchoscopy. - Fabry, Ben; Bonakdar, Navid; Kuster, Christian; Bartl, Johannes; Krischke, Frederick; Francis, Roland (Intensive Care Medicine Experimental, 2025)
BACKGROUND: Bronchoscopy in ventilated patients narrows the endotracheal tube lumen and increases resistance, which can lead to hypoventilation and intrinsic PEEP build-up. These ventilation impairments depend on the geometry of the tube-bronchoscope combination, ventilator settings, and patient mechanics. Currently, no predictive method exists to quantify these impairments or guide compensatory strategies. METHODS: We measured pressure-flow relationships across multiple tube-bronchoscope configurations in a bench setup and derived a scaling law describing the nonlinear, flow-dependent resistance as a function of the effective tube diameter, defined as the diameter of a circular tube with the same open cross-sectional area as the remaining lumen. We then assessed the ventilatory consequences of bronchoscopy using an intensive care ventilator connected to an active lung simulator under both volume- and pressure-controlled modes. RESULTS: Bronchoscope insertion sharply increases resistance, which scales with the inverse fifth power of the effective diameter. A simulation tool based on this scaling law accurately predicts the experimentally observed dynamic hyperinflation and intrinsic PEEP build-up in volume-controlled modes, as well as the reduced tidal volumes in pressure-controlled modes. Ventilation with automatic tube compensation during pressure control fully prevents both impairments. CONCLUSIONS: The commonly cited recommendation of a ≥ 2 mm difference between endotracheal tube and bronchoscope diameters does not reliably prevent ventilation impairments during bronchoscopy. Our findings suggest that a quantitative framework, which accounts for ventilator settings, patient mechanics, and the effective tube diameter, can provide additional guidance for tube selection and help anticipate impairments. We demonstrate proof of principle that pressure-controlled ventilation with automatic tube compensation is a feasible strategy to mitigate bronchoscopy-induced ventilation impairments.
EVALuna2:613111